Varela, Ma Ángeles; Barnés, Antonio; Nila Martínez, Alicia y Rafael Ruiz Andrés (eds.) (2022): Autores en busca del autor. Volumen II, CEU Ediciones, Madrid, 275 pp., ISBN 978-84-19111-40-1. - Katilina Espi , Ekaterina (’Ilu. Revista de Ciencias de las Religiones, 2024)
C’est un compte rendu.